Oscillations of point-supported square slabs - A. G. Abovyan; A. S. Marutyan; G. A. Abovyan (Stroitel’stvo: Nauka i Obrazovanie, 2023)
Introduction. The development of methods for determining the frequencies and forms of vibrations, as well as dynamic reactions of thin slabs with different support systems, including those supported on point supports, is an urgent task, the solution of which is the subject of this paper.The aim of the work is to develop experimental methods for determining the frequencies and forms of natural vibrations of thin point-supported square solid slabs and slabs with holes.Materials and methods. The methodology and analysis of experimental results of dynamic characteristics of square solid slabs and slabs with holes are presented.Results. In this work, the frequencies of natural vibrations of square slabs with free edges resting on point supports are determined; the dependences of frequencies of slabs vibrations on coordinates of point supports and sizes of symmetrically located holes are obtained; the location of point supports at which the fundamental frequency of slabs free vibrations is maximum, is determined; frequencies, forms and decrements of vibrations of square slabs resting on four point supports are experimentally determined, as well as the influence of presence of holes and the degree of pinching of the supports on the dynamic characteristics of these slabs.Conclusions. Comparison of experimental and theoretical values of natural vibration frequencies of the slabs showed good similarity. The results obtained in this paper can be appplied to dynamic and seismic calculations of point-supported square slab coverings.